Rancang Bangun dan Pengujian Oven Pemanas Baja Kapasitas 1200oc - Aprizal, Aprizal; Arifin, Yayan (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Heating ovens are equipment used to heat up materials and change their shape (stretching, heating) or changing properties (heating). Can also be called an oven or Klin. Transferring energy to the oven occurs in the stage of generation of heat energy by a heating element whose energy is supplied from electricity. This heat treatment is designed with materials that can withstand temperatures of 1200oC. The design of heat treatment steel heaters as a means to conduct heat treatment labs. The results of making these ovens contain skeletons, inner walls, outer walls or casings, doors. This steel heater oven is supported by spiral coil heating components, thermocouple (temperature sensor), glass wholl, digital temperature control, timer control. This machine uses a 3 x 3 cm hollow iron frame with 6000 watts of electricity. The number of heaters used is 1 heating rod with a length of 200 cm and an outer diameter of 9.64 mm. The size of the oven is wide, 44 cm, width 42 cm, and height of 38 cm